FAKTOR â FAKTOR DOMINAN PEMBENTUK TINGKAT VISUAL APPROPRIATENESS FASADE BANGUNAN PADA KORIDOR KOMERSIAL JALAN SAGAN â JALAN PROF. DR. IR. HERMAN YOHANES - , Octavianus Henry Set ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Commercial activity grows fast in Jalan Sagan â Jalan Prof. DR. Ir. Herman Yohanes corridor, created various changes on the character of the city space especially on the visual performance of the buildings on both side of the street. The demand of the commercial, efficiency, and need for economic changes the function of buildings that have an impact on character changes of the area. In the end, expression from each building brought formed by their function and way to attract visitor attention. By looking at the phenomenon exists, this study aimed to determine the visual appropriateness level of the building faÃ§ade layout along Jalan Sagan â Jalan Prof. DR. Ir. Herman Yohanes corridor and the dominant factors its formed so that the results which are expected to help formulating a direction for future development. This research is a specific study about the buildings faÃ§ade layout along Jalan Sagan â Jalan Prof. DR. Ir. Herman Yohanes corridor through the rationalistic qualitative approach. This research uses visual appropriateness theories by Bentley., et al., (1985) in his book Responsive Environments â A Manual for Designer as main theories. Analysis was focused in contextual cues related to buildings faÃ§ade layout in physical context divided on two parts, such as: buildings faÃ§ade elements and relationhips between buildings faÃ§ade elements. Analysis is done by using graphic method and started with data describing about building faÃ§ade elements that consist of wall material (texture, color, signage) and doors â windows with relationships between building faÃ§ade elements that consist of vertical rhythms